Brucellosis in cattle and micro-scale spatial variability of pastoral household income from dairy production in south western Uganda - Nina, Pius Mbuya; Mugisha, Samuel; Leirs, Herwig; Basuta, Gilbert Isabirye; Van Damme, Patrick (Acta tropica, 2017)
Brucellosis in cattle and humans has received world-wide research attention as a neglected and re-emerging zoonotic disease with many routes of transmission. Studies of brucellosis in Uganda have emphasized occupational exposures and also revealed variations in prevalence levels by region and cattle production systems. To date, research linking pastoralist household income from dairy production to brucellosis and its transmission risk pathways do not exist in Uganda. We assessed whether spatial differences in unit milk prices can be explained by brucellosis prevalence in cattle along a distance gradient from Lake Mburo National Park in Uganda. Semi-structured interviews administered to 366 randomly selected household heads were supplemented with serological data on brucellosis in cattle. Statistical analysis included Pearson correlation test, multiple regression and analysis of variance (ANOVA) using SPSS version 17. Serological results showed that 44% of cattle blood samples were sero-positive for brucellosis. The results obtained from interviews put the statistical mean of household reported cattle abortions at 5.39 (5.08-5.70 at 95% CI, n=366). Post-hoc analysis of variance revealed that both sero-positive cattle and reported cattle abortions significantly were much lower when moving outwards from the park boundary (p<0.05), while the price of milk increased significantly (p<0.05) along the same distance gradient. Further studies should identify public and private partnerships needed to create and strengthen good zoonotic brucellosis management practices at the nexus of wildlife and livestock in Uganda.
Keywords: Livestock; brucelóza; skot; Female; Humans; mlékárenství; Milk; lidé; nemoci skotu; Uganda; ženské pohlaví; těhotenství; riziko; Prevalence; Dairying; Animals; Risk; Cattle Diseases; zvířata; dobytek; Brucellosis; Pregnancy; Cattle; prevalence; prostorová analýza; mléko; Spatial Analysis